Pandangan Negara Integralistik sebagai Dasar Philosofische Gronslag Negara Indonesia - Riski Febria Nurita; Laga Sugiarto (University of Merdeka Malang, 2018)
The idea of an integralistic state of Indonesia that embraces Unity becomes a soul rather than the conception of the form of the Unitary State of the Republic of Indonesia (NKRI), its relationship with the Pancasila can be seen that the Pancasila is a unified whole that cannot be separated. Each precept cannot be separated from one another, the whole precepts describe the existence of a unity or integralistic notion that is in accordance with the spirit of Unity in Diversity. The type of writing used in this paper is Normative Jurisdiction. We can see the assertion of its own integralistic state of understanding and we describe it in the formulation of the One Sila and the third Sila of the Pancasila. Countries that are based on family life, will organize the foundation not only inward, but also outside. Even though the idea of an integralistic state is the idea of a nation state (nationale staat), it does not mean that the Indonesian nation with all the reasons for narrow nationalism (chauvinism) takes actions that can demean other nations by assuming that Indonesia is the only nation that feels superiority and dignity superior to other nations.How to cite item: Nurita, R., Sugiarto, L. (2018). Pandangan Negara Integralistik sebagai Dasar Philosofische Gronslag Negara Indonesia. Jurnal Cakrawala Hukum, 9(1), 59-67. doi:https://doi.org/10.26905/idjch.v9i1.1986